Investigation of Optimum Insulation Thickness in The Wall With Air-Cavity and The Environmental Analysis - Özel, Meral; Şengür, Serhat; Özel, Cihan (Bitlis Eren Üniversitesi, 2026)
Making energy efficient designs in building walls can be a solution to reduce increasing building energy consumption and thus environmental pollution. By using insulation and energy efficient building materials, the heating and cooling loads of buildings and therefore fuel consumption and environmental pollution can be significantly reduced. Therefore, this paper goals to evaluate the thermal, economic and environmental effects of walls with air-cavities by considering different wall orientations. The study uses a numerical method called the implicit finite difference procedure to compute annual transmission loads for walls that have and haven't air-cavities during the summer and winter seasons in Elazığ province of Turkey. The conclusions show that the annual cooling and heating loads decline by about 31% for all wall orientations when a 2.5 cm air-cavity is positioned in the center of an uninsulated concrete wall. The study also shows that the effect of the air-cavity on heat transmission loads declines as insulation thickness rises. Additionally, walls incorporating air cavities were analyzed to determine their annual average time lag and decrement factor. To identify the optimal insulation thickness, a cost analysis was conducted using annual transmission loads calculated under dynamic thermal conditions. The findings indicate that the most effective insulation thicknesses for walls with air cavities are 12.4 cm for south-facing orientations, 13.2 cm for north-facing, and 13.4 cm for east- and west-facing orientations. When these optimal values are applied across all orientations, the annual heating energy, fuel consumption, and associated emissions are reduced by 87.3%, 87.9%, and 88.0%, respectively.
Keywords: Mechanical Engineering (Other); Makine Mühendisliği (Diğer)